The Control of Externalities in Sports Leagues: An Analysis of Restrictions in the National Hockey League - Carlton, Dennis W.; Frankel, Alan S.; Landes, Elisabeth M. (Journal of Political Economy, 2004)
This paper provides one of the few successful demonstrations of the efficiency of certain types of restrictions in the context of a joint venture. The joint venture we examine is the National Hockey League (NHL) in the 1980s, which was then composed of 21 separately owned teams. (It now has 30 teams.) The restriction we analyze is the NHL rule on franchise relocation. Before one can fully understand the effect of the restriction, one must understand the theory of how sports leagues operate and whether sports leagues have any market power that can be enhanced by such a restriction. After providing such a theory, we empirically test the effect of the NHL restriction on franchise relocation. Aside from data availability, the advantage of our time period is that television was then an unimportant source of revenue for the NHL. Thus we are able to isolate a particular externality arising from how the NHL finances teams.